Clinical features of children with multicystic dysplastic kidney - Kara, Aslihan; Gurgoze, Metin Kaya; Aydin, Mustafa; Koc, Zehra Pinar (Wiley, 2018)
BackgroundTo evaluate the clinical features of patients with multicystic dysplastic kidney (MCDK). MethodsThe medical files of children diagnosed with MCDK between January 2008 and November 2015 were retrospectively reviewed. The demographic, clinical, laboratory and radiological data were evaluated. ResultsOf 128 children with MCDK enrolled in the study, 82 (64.1%) were male, and 46 (35.9%) were female (P< 0.05). MCDK were located on left and right sides in 66 (51.6%) and 62 children (48.4%), respectively (P > 0.05). Antenatal diagnosis was present in 64 patients (50%). The mean age at diagnosis was 2.8 2.7years (range, 0-8years), and follow-up duration was 4.5years. Fifteen patients (20.8%) had vesicoureteral reflux. Of these, four underwent endoscopic surgical correction. Other associated urological anomalies were ureteropelvic junction obstruction (n = 6), hypospadias (n = 1), and kidney stones (n = 1). On technetium-99m dimercaptosuccinic acid scintigraphy, which was performed in all patients, no significant association between grade of reflux and presence of scarring was seen. Hypertension was diagnosed only in one child (0.8%) who required antihypertensive treatment. The prevalence of unilateral undescended testicle in children aged <1year in the 82 male patients was 4.9%. Seventy-six patients (59.4%) developed compensatory hypertrophy in the contralateral kidney during a 1year follow-up period. Of the total, only seven children (5.5%) had undergone nephrectomy. ConclusionsMCDK follows a benign course with relatively few sequelae, and therefore these patients should be closely followed up and conservatively managed.
Keywords: morbidity; multicystic dysplastic kidney; renal cystic disease; urinary tract malformation; vesicoureteral reflux